Culture and bank reputation - Gunawan, Henry; Khomsiyah, Khomsiyah; Augustine, Yvonne (Technium Social Sciences Journal, 2022)
The study examines and analyzes the relationship between culture and reputation in the banking industry in Indonesia. To attain this destination, we utilize the employees working in the banks as the sample by snowball sampling. As a result, this research can get 435 responses based on the survey conducted in November 2021. Furthermore, these obtained responses are analyzed by a structural equation model based on variance or partial least squares to examine the proposed hypothesis. Based on this model, this study demonstrates that indicators of bank reputation and all dimensions of culture: mission, adaptability, clan, and bureaucracy, and their items are accurate and reliable based on confirmatory factor analysis and reliability detection. Based on the hypothesis testing, this study reveals a positive tendency of bank culture on reputation.